Finger competition dynamics in rotating Hele-Shaw cells - Gadêlha, H; Miranda, J (2004)
The development of interfacial instabilities in rotating Hele-Shaw cells were investigated. A differential equation describing the early nonlinear evolution of the interface was also derived, in terms of three relevant dimensionless parameters which are viscosity contrast A, surface tension B, and gap spacing b. It was found that the link between finger competition and A, B, and b can be revealed by a mechanism based on the enhanced growth of subharmonic perturbations. The condition of vanishing A was found to suppress the dynamic competition between fingers, regardless of the value of B and b.